2019
DOI: 10.1002/capr.12287
|View full text |Cite
|
Sign up to set email alerts
|

What do clinical supervision research reviews tell us? Surveying the last 25 years

Abstract: What do clinical supervision research reviews across the last 25 years tell us? That question is subsequently examined. Based on database and literature searches, 20 reviews appearing from 1995 through 2019 were identified for survey examination; consistencies, inconsistencies and other defining features were determined across reviews; and the survey findings and their implications are considered. Primary findings are as follows: (a) ‘proof’ for supervision appears to be more ‘proof by association’ than otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 59 publications
3
33
0
8
Order By: Relevance
“…This review found various methodological concerns across many studies reviewed, which is consistent with findings from a recent survey of 20 systematic reviews on clinical supervision reported between 1995 to 2019 [3]. Methodological concerns include predominance of ex post facto, cross-sectional, correlational designs, small sample sizes, over reliance on self-report measures, lack of psychometrically sound supervision measures, and lack of experimental and longitudinal designs [3].…”
Section: Plos Onesupporting
confidence: 78%
See 3 more Smart Citations
“…This review found various methodological concerns across many studies reviewed, which is consistent with findings from a recent survey of 20 systematic reviews on clinical supervision reported between 1995 to 2019 [3]. Methodological concerns include predominance of ex post facto, cross-sectional, correlational designs, small sample sizes, over reliance on self-report measures, lack of psychometrically sound supervision measures, and lack of experimental and longitudinal designs [3].…”
Section: Plos Onesupporting
confidence: 78%
“…Healthcare organisations also need to support clinical supervisors to build and foster positive supervisory relationships with their supervisees. This has commonly been reported to be the single most important factor that influences the effectiveness of clinical supervision [3,11,54], and requires investment of both time and resources. Supervisors and supervisees can also be guided by evidence-informed principles that facilitate effective clinical supervision.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Clinical supervision is essential to psychotherapists' professional development Falender and Shafranske (2004); Orlinsky and Rønnestad (2005) and to monitoring the quality of client care that supervisees provide (Goodyear, Falender, & Rousmaniere, 2017). Commensurate with its importance, a robust literature has emerged to inform our understanding of supervision processes (Bernard & Goodyear, 2019) and impacts (see e.g., Allan, McLuckie, & Hoffecker, 2017;Watkins Jr., 2020;Wheeler & Richards, 2007), as well as expected supervisory best practices (American Psychological Association, 2014Association, , 2015Borders et al, 2014;Ellis et al, 2014). However, the focus of this literature has been primarily on the supervision of trainees, with only a very few studies focusing on the supervision of practicing psychologists.…”
Section: Introductionmentioning
confidence: 99%